Gambaran Faktor Risiko pada Pasien Hernia Inguinalis di RSUD Buleleng Tahun 2019-2020 - I Gede Ryan Widhi Wirajaya; Sri Ratna Dewi; Sang Nyoman Suriana (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
An inguinal hernia is a protrusion of abdominal contents from a normal cavity that occurs in the abdominal wall in the inguinal region. Hernias are divided into lateral inguinal hernias and medial inguinal hernias. The incidence of hernia can be influenced by modifiable factors such as obesity, diabetes, smoking, use of immunosuppressants and non-modifiable factors, namely age and gender. Hernias are caused by conditions that cause an intra-abdominal increase such as chronic cough, constipation, heavy lifting, and abdominal malignancy or weakness of the abdominal muscles. The aim of this study was to assess the description of risk factors of inguinal hernia patients at Buleleng Hospital. The method used was descriptive and a cross sectional approach. The number of samples in this study is 45 samples that has met the criteria. Data obtained will be collected, processed, and presented in the form of tables and descriptive narratives. The results in this study showed that the final elderly age group in the range of 56-65 years was 16 (35.6%) subjects, working as laborers were 16 (35.6%) subjects, based on gender, 43 (95) were male. (6%) subjects, and 31 (68.9%) subjects had a history of chronic cough.